Agensi Pekerjaan Dream-Job Sdn Bhd / Anisa Zurani Abdullah - Abdullah, Anisa Zurani (Faculty of Business and Management, 2023)
This report is the culmination of my programme for internships as part of the Industrial Training Programme (MGT666). This report is the culmination of my six-month apprenticeship in the fields of marketing and sales at Agensi Pekerjaan Dream-Job SDN BHD. This is an overview report highlighting my real-life day-to-day involvement in the tasks assigned by the leader, my role of the Sales and Marketing field journey, and some of the business activities of Agensi Pekeijaan Dream-Job SDN BHD. This internship report emphasises the major projects I accomplished, both academic and non-academic in nature. The objective of this final report is to recognise along with the details of the company's profile, training reflection, SWOT Analysis, discussion and recommendations, projects completed, experience gained, and accomplishments of the intern. On the first of March 2023,1 was assigned to Agensi Pekeijaan Dream-Job SDN BHD and will remain there until the 15th of August 2023 to complete my apprenticeship. I consider myself blessed to have worked in such a fantastic workplace as Agensi Pekeijaan Dream-Job SDN BHD, where I got exposed to new terms, technologies, and the reality of how business to business (B2B) operations work. The assignments on which I concentrated undoubtedly assisted me to expand the depth of my real-world expertise in Sales and Marketing. The study and development tasks were especially valuable in growing my viewpoints on assisting providing information about manpower supply and the service we provide, improving conversation skills with prospects and always building and maintaining relationships with prospects. Throughout my journey as an intern at this company, of course I have learned a lot of new knowledge, but there are also obstacles and difficulties that I must face from day to day. This problem has been taken as advice and used as a lesson to improve my knowledge and skills in the future. With this internship program, I have more experience and know about various information when conducting B2B business.